Rice gall dwarf virus exploits tubules to facilitate viral spread among cultured insect vector cells derived from leafhopper Recilia dorsalis - Chen, Hongyan; Zheng, Limin; Jia, Dongsheng; Zhang, Peng; Chen, Qian; Liu, Qifei; Wei, Taiyun (Frontiers in Microbiology, 2013)
Rice gall dwarf virus (RGDV), a member of the family Reoviridae, causes repeated epidemics in rice fields in southern China. An RGDV isolate collected from Guangdong Province (southern China) is mainly transmitted by leafhopper vector Recilia dorsalis in a persistent-propagative manner. The infection by RGDV induces the formation of virus-containing tubules in the plant host and insect vector. In this study, we established continuous cell cultures of the leafhopper R. dorsalis to investigate the functional role of these tubules within the insect vector. Cytopathologic studies revealed that the tubules, which comprised viral nonstructural protein Pns11 and contained viral particles, were able to protrude from the surface of cultured leafhopper cells. Tubule-like structures formed in nonhost insect cells after the expression of Pns11 in a baculovirus system, suggesting that Pns11 was the minimal viral factor required for the formation of the tubules induced by RGDV infection. In cultured leafhopper cells, knockdown of Pns11 expression from RNA interference, induced by synthesized dsRNA from the Pns11 gene, abolished the formation of such tubules, preventing the direct cell-to-cell spread of RGDV without significant effects on viral multiplication. All these results show that RGDV exploits virus-containing tubules to facilitate viral spread among its insect vector cells.